Marcadores conversacionais como elementos constitutivos da interação em sala de aula (Elocuções Formais – Projeto NURC-SP) - Souza, Emiliane Gil Nunes de (2017)
The language spoken is the first contact to which we have access in language acquisition. Snorted and speech through it in we as subjects in the conversational interactions. Understanding the mechanisms of language spoken in boosted to develop the theme of this research. Anchored by the theory of conversation Analysis, we analyze in this work, a most peculiar element to speak, being most often used in informal talks: conversational markers. We recognize that these markers can be found in more formal contexts, including in matters of particular manner: the classroom. It is well known that, in this event, there is a communicational formality in the manner of speaking of the interactantes it involved: teacher and students. Considering factors such as: the class model predominantly expository; the time of possession shifts established the professor and the asymmetric relationship between the interlocutors, it is noted that the conversational markers play various functions that assist in the global Constitution that conversational interaction. Urged us to investigate the functioning of these markers and the way they help in the Organization of speech of professor in the classroom. The results obtained show that the use of markers, this kind of interaction, it is inevitable and essential, due to constant need for adjustments in the Organization of speech of professor, during the explanation of the topic in class. We believe that this work may help teachers/researchers, not only by theoretical approach in which underpin us to the study of the spoken language, but above all to serve as a source for further research